OPTIMIZING WORKERS' RIGHTS IN THE DYNAMICS OF WORK FROM HOME: AN OVERVIEW OF THE PRINCIPLES OF EMPLOYMENT DEVELOPMENT IN INDONESIA - Khoirunnisa; Didi Jubaidi (Jurnal Humaniora & Sosial Sains, 2024)
The work from home trend is increasingly popular throughout the world. In Indonesia, the internet has contributed to the development of the work from home trend, because the internet network is very easy. However, various existing regulatory provisions tend to only regulate matters related to office work, while the rights and obligations of employers in the work from home scheme are never specifically regulated. The purpose of this study is to analyze the suitability of the work agreement with the fulfillment of the rights of workers who work remotely from home from the perspective of law and regulations and the principles of employment development. The approach method in this study is a sociological legal approach. The findings of this study indicate that the fulfillment of workers' rights, both those stated in the contract and in their realization are important factors in the fulfillment of workers' rights that are not fully in accordance with the principles that support employment development.